Prevalência da toxoplasmose gestacional e avaliação do esquema terapêutico em Gurupi-Tocantins - Sousa, Sara Falcão de (2020)
Toxoplasmosis is characterized by a protozoosis caused by Toxoplasma gondii (T. gondii). It is a disease that causes a great impact on human health due to its high risk of vertical transmission and fetal involvement, which can compromise the health and development of the baby, before or after birth. Of great impact on human health, toxoplasmosis requires screening, diagnosis and appropriate treatment to avoid or minimize its potential damage. The objective of this study was to quantify the prevalence of toxoplasmosis in pregnant women in the municipality of Gurupi-TO and to compare the effectiveness of spiramycin in the treatment of the congenital form of the disease, as well as the sequelae existing in infected neonates. A descriptive, epidemiological, observational and cross-sectional study was carried out, in which 309 medical records of pregnant women monitored in Basic Health Units in Gurupi-Tocantins from 2010 to 2017 were analyzed, in order to describe the seroepidemiology of the disease. 30 medical records of pregnant women treated with different medication regimens were also analyzed, investigating the children's serology after birth and the presence or absence of sequelae related to congenital toxoplasmosis. Regarding sociodemographic characteristics, it was observed that the majority of pregnant women, 58.57 %% (n = 181) were between 20 and 30 years old, 172 (55.6%) were married, 55.0% (n = 170) had one or two pregnancies and 66.0% (204) were between the first and the second trimester of pregnancy. Analyzing the results of serology for toxoplasmosis, it was observed that the prevalence for gestational toxoplasmosis was 30.1% (n = 93), and in 16.12% (n = 50) of the records analyzed, the result of serology has not been demonstrated and in 20.7% (n = 64) of women, T. gondii infection was active or recent. The positive impact of continued treatment throughout the pregnancy was observed since of the 15 children, children of mothers who were treated during the whole pregnancy with spiramycin, only 1 had positive serology for toxoplasmosis after birth. On the other hand, of the 15 children gestated by the mothers who belonged to the group of pregnant women who were treated with spiramycin for only 2 months after the diagnosis of the disease, in which 13 babies presented positive serology, indicating congenital toxoplasmosis. The most frequent sequelae observed in these children were: chorioretinitis (80%) and delayed motor development (53%). These findings show that Gurupi-TO was shown to be a municipality with a high endemicity of this parasite, resulting in a warning signal both for the number of toxoplasma infections during pregnancy as well as for the high number of pregnant women susceptible to infection. It is also noteworthy that the continued prenatal treatment for toxoplasmosis with the use of spiramycin proved to be a strong ally in preventing sequelae in children in this population after birth.